Bibliometric Analysis of the Implementation of Character Education in the School Curriculum - Nanny Mayasari; Petrus Ambarura; Tarpan Suparman; Imas Indah Mutiara; I Gusti Ayu Niken Launingtia (West Science Interdisciplinary Studies, 2024)
This bibliometric analysis investigates the evolution and thematic structuring of research concerning the implementation of character education in school curricula. Utilizing data sourced from major academic databases from 1893 to 2024, this study maps out the academic discourse through VOSviewer. Our findings identify distinct thematic clusters such as curriculum integration, ethical considerations, and the role of character education within religious and civic education. Temporal trends indicate a shift from foundational discussions to a focus on the implicit dimensions of character education, such as the hidden curriculum and character-building across educational levels. Potential future research opportunities were identified in less explored areas such as independent and culturally specific curricula. The analysis of the author collaboration network reveals a robust community with significant interconnections among key scholars, highlighting both dense clusters and emerging researchers. Overall, this study offers a comprehensive overview of the field, demonstrating its dynamic evolution and the collaborative nature of research that contributes to ongoing debates and educational practices in character education. This work not only charts historical and current trends but also provides direction for future scholarly endeavors in this vital area of educational research.